Work from Home in Pandemic - An Indian Perspective - Khatun, Rizwana (Inverge Journal of Social Sciences, 2023)
With lockdowns consequent to the outbreak of the COVID-19 pandemic, most people were confined to their homes, along with their children and many of the vulnerable elderly. The spill-over effect of the pandemic brought about rampant changes in the lives of all, with working from home being a major one. This study was done to find the perspective and experiences of the Indian workforce after two years of working from home, with many still pursuing the same format. Also, it was intended to assess the personal factors contributing to one’s willingness to continue to work from home post-pandemic. The chi-square test and the SPSS ordinal regression procedure were employed to test the hypotheses defined for achieving the objectives of the study. The study found that the experiences and challenges faced by both males and females were significantly different, with females facing greater stress. For males, working from home was more pleasant. However, they faced difficulty maintaining a work-life balance. While gender was insignificant, age and having no children, particularly less than ten years old, were significant predictors of willingness to work from home in the post-pandemic era. References Abdullah, N. A., Rahmat, N. H., Zawawi, F. Z., Khamsah, M. A., & Anuarsham, A. H. (2020). Coping with Post Covid-19: Can Work from Home be a New Norm? European Journal of Social Sciences Studies, 61-81. Agresti, A. (1981). Measures of Nominal-Ordinal Association. Journal of the American Statistical Association, 524-529. Aldossari, M., & Chaudhry, S. (2021). Women and Burnout in the Context of a Pandemic. Gender, Work & Organization, 826-834. Allen, T. D., Golden, T. D., & Shockley, K. M. (2015). How Effective Is Telecommuting? Assessing the Status of Our Scientific Findings. Psychological Science in the Public Interest, 40-68. Alon, T., Doepke, M., Olmstead-Rumsey, J., & Tertilt, M. (2020). The Impact of the Coronavirus Pandemic on Gender Equality. Covid Economics Vetted and Real-Time Papers, 62-85. Angelici, M., & Profeta, P. (2020). Smart-working: Work Flexibility Without Constraints. Milan: Università Bocconi & The Dondena Centre: Working Paper No. 137. Asif, M., Pasha, M. A., Shafiq, S., & Craine, I. (2022). Economic Impacts of Post COVID-19. Inverge Journal of Social Sciences, 1(1), 56-65. Beniwal, V. (2020, June 26). The Virus Has Made India’s Devastating Gender Gap Even Worse. Retrieved from Bloomberg: https://www.bloomberg.com/news/features/2020-06-25/india-coronavirus-lockdown-hits-women-hard-worsening-gender-gap#xj4y7vzkg Berniell, I., Berniell, L., De la Mata, D., Edo, M., & Marchionni, M. (2021). Gender Gaps in Labor Informality: The Motherhood Effect. Journal of Development Economics, 102599. Bick, A., Blandin, A., & Mertens, K. (2020). Work from Home After the COVID-19 Outbreak. Dallas: Federal Reserve Bank Dallas. Working Paper. Bloom, N., Liang, J., Roberts, J., Ying, & Jenny, Z. (2015). Does Working from Home Work? Evidence from a Chinese Experiment. The Quarterly Journal of Economics, 165–218. Boris, E. (2019). Homework in the Past, it’s Meaning for the Future. In K. E. Christensen, The New Era of Home-based Work- Directions and Policies. Routledge. Buffer & AngelList . (2020). The 2020 State of Remote Work. Buffer & AngelList . Chattopadhyay, S. (2021). The Pandemic of Productivity- The Work of Home and the Work from Home. Anthropology in Action- Journal for Applied Anthropology in Policy and Practice, 47-51. Chauhan, P. (2022). “I Have No Room of My Own”: COVID-19 Pandemic and Work-From-Home Through a Gender Lens. Gender Issues, 507-533. Collins, C., Landivar, L. C., Ruppanner, L., & Scarborough, W. J. (2020). COVID-19 and the Gender Gap in Work Hours. Gender Work Organization, 1–12. Crowson, M. (2019, july 15). Ordinal logistic regression using SPSS. Retrieved from YouTube: https://www.youtube.com/watch?v=rSCdwZD1DuM Cummings, M. (2020, July 17). Study Reveals Gender Inequality in Telecommuting. Retrieved from YaleNews: https://news.yale.edu/2020/07/17/study-reveals-gender-inequality-telecommuting De Klerk, J. J., Joubert, M., & Mosca, H. F. (2021). Is Working from Home the New Workplace Panacea? Lessons from the COVID-19 Pandemic for the Future World of Work. SSA Journal of Industrial Psychology, 1-14. Del Boca, D., Oggero, N., Profeta, P., & Rossi, M. (2020). Women’s and Men’s Work, Housework and Childcare, Before and During COVID-19. Review of Economics of the Household, 1001–1017. Deniz, M. E., Satici, S. A., Doenyas, C., & Griffiths, M. D. (2022). Zoom Fatigue, Psychological Distress, Life Satisfaction, and Academic Well-Being. Cyberpsychology, Behavior, and Social Networking, 270-277. Dizaho, E. K., Salleh, R., & Abdullah, A. (2017). Achieving Work Life Balance through Flexible Work Schedules and Arrangements. Global Business and Management Research: An International Journal, 455. Eddleston, K. A., & Mulki, J. (2017). Toward Understanding Remote Workers’ Management of Work–family Boundaries: The Complexity of Workplace Embeddedness. Group & Organization Management, 346-387. Esquivel, A., Marincean, S., & Benore, M. (2023). The Effect of the Covid-19 Pandemic on STEM Faculty: Productivity and Work-life Balance. PlosOne, 18, e0280581. Ford Media Centre. (2015, April 27). For Europeans, the Journey to Work Causes More Stress Than Their Actual Jobs (or Even The Dentist), New Ford Survey Shows. Retrieved from Ford Media Centre: https://media.ford.com/content/fordmedia/feu/en/news/2015/04/27/for-europeans--the-journey-to-work-causes-more-stress-than-their.html#:~:text=The%20Ford%20European%20Commuter%20Survey%20of%205%2C503%20commuters,of%20stress%20than%20moving%20into%20a%20new Fosslien, L., & Duffy, M. W. (2020, April 29). How to Combat Zoom Fatigue. Harvard Business Review. Franke, T. M., Ho, T., & Christie, C. A. (2012). The Chi-square Test: Often Used and More Often Misinterpreted. American Journal of Evaluation, 448-458. Friedman, S. (2015). Still a “stalled revolution”? Work/family Experiences, Hegemonic Masculinity, and Moving Toward Gender Equality. Sociology Compass, 140-155. Gelles, D. (2020, June 23). Are Companies More Productive in a Pandemic? Retrieved from The New York Times: https://www.nytimes.com/2020/06/23/business/working-from-home-productivity.html Georgieva, K., Fabrizio, S., Lim, C. H., & Tavares, M. M. (2020). The COVID-19 Gender Gap. IMF. Gorlick, A. (2020, March 30). Productivity Pitfalls of Working from Home in the Age of COVID-19. Stanford News. Retrieved from Stanford Institute for Economic Policy Research. Grant, C. A., Wallace, L. M., Spurgeon, P. C., Tramontano, C., & Charalampous, M. (2019). Construction and Initial Validation of the e-Work Life Scale to Measure Remote e-Working. Employee Relations , 16–33. Haider, F. (2020, September 01). Average Indian Saving Almost Two Hours of Commute Time While Working from Home: Survey. Retrieved from The Economics Times: https://economictimes.indiatimes.com/jobs/working-from-home-saves-rs-5520-per-month-for-an-average-professional-in-india/articleshow/77850500.cms Hassan, H., & Nuruddin, A. R. (2011). Working From Home Concept for Quantity Surveying Employment. The Quantity Surveying International Convention 2011, (pp. 127-135). Penang, Malaysia. Hennekam, S., & Shymko, Y. (2020). Coping with the COVID-19 Crisis: Force Majeure and Gender Performativity. Gender, Work and Organization, 788-803. Hjálmsdóttir, A., & Bjarnadóttir, V. S. (2021). “I have turned into a foreman here at home”: Families and Work–life Balance in Times of COVID-19 in a Gender Equality Paradise. Gender, Work & Organization, 268-283. IANS. (2020, April 14). Work from Home is Making 67% Indians Suffer from Sleep Deprivation, Says Study. Retrieved from Times of India: https://timesofindia.indiatimes.com/life-style/relationships/work/work-from-home-is-making-67-indian-suffer-from-sleep-deprivation-says-study/articleshow/75126242.cms ILO. (2020). An Employers’ Guide on Working from Home in Response to the Outbreak of COVID-19. Geneva: International Labour Organization. Israni, M., & Kumar, V. (2021). Gendered Work and Barriers in Employment Increase Unjust Work–Life Imbalance for Women: The Need for Structural Responses. The International Journal of Community and Social Development, 290–295. Jóhannsdóttir, Á. (2018). Young Femininity in Iceland and its Discontents. Psychology of Women Section Review- British Psychological Society, 17-30. Kamdar, B. (2020, July 31). Women Left Behind: India’s Falling Female Labor Participation. Retrieved from The Diplomat: https://thediplomat.com/2020/07/women-left-behind-indias-falling-female-labor-participation/ Kaspersky. (2020). How COVID-19 Changed the Way People Work. AO Kaspersky Lab. Kaur, T., & Sharma, P. (2020). A Study on Working Women and Work from Home Amid Coronavirus Pandemic. Journal of Xi'an University of Architecture & Technology, 1006-7930. Kazekami, S. (2020). Mechanisms to Improve Labor Productivity by Performing Telework. Telecommunications Policy, 101868. Koziol, N. A., & Bilder, C. R. (2014). MRCV: A Package for Analyzing Categorical Variables with Multiple Response Options. R Journal, 144-150. Kramer, A., & Kramer, K. Z. (2020). The Potential Impact of the Covid-19 Pandemic on Occupational Status, Work from Home and Occupational Mobility. Journal of Vocational Behavior, 119. Lachapelle, U., Tanguay, G. A., & Neumark-Gaudet, L. (2018). Telecommuting and Sustainable Travel: Reduction of Overall travel Time, increases in Non-motorised Travel and Congestion Relief? . Urban Studies, 2226–2244. Lavassani, K. M., Movahedi, B., & Kumar, V. (2009). Development in Analysis of Multiple Response Survey Data in Categorical Data Analysis: The Case of Enterprise System Implementation in Large North American Firms. Journal of Applied Quantitative Methods, 45-53. Lavelle, J. (2020, April 3). Gartner CFO Survey Reveals 74% Intend to Shift Some Employees to Remote Work Permanently. Retrieved from Gartner : https://www.gartner.com/en/newsroom/press-releases/2020-04-03-gartner-cfo-surey-reveals-74-percent-of-organizations-to-shift-some-employees-to-remote-work-permanently2 Lund, A., & Lund, M. (2018). Ordinal Regression using SPSS Statistics. Retrieved from Laerd Statistics: https://statistics.laerd.com/spss-tutorials/ordinal-regression-using-spss-statistics.php Lupu, V. L. (2017). Teleworking and Its Benefits on Work-Life Balance. International Multidisciplinary Scientific Conference on Social Sciences & Arts, SGEM, 693-700. Lyttelton, T., Zang, E., & Musick, K. (2020). Gender Differences in Telecommuting and Implications for Inequality at Home and Work. SSRN 3645561. Mandavia, M., & Chandrashekhar, A. (2020, June 21). India Inc Suffers a New Ailment, Complains of Webinar Fatigue, Zoom Gloom. Retrieved from The Economic Times: https://economictimes.indiatimes.com/news/company/corporate-trends/india-inc-suffers-a-new-ailment-complain-of-webinar-fatigue-zoom-gloom/articleshow/76496912.cms Mccloskey, D. (2018). An Examination of the Boundary Between Work and Home for Knowledge Workers. International Journal of Human Capital and Information Technology Professionals, 25–41 . Mirela, B. (2020). The Impact of Working from Home on Productivity. A Study on The Pandemic Period. Annals of the University of Oradea, Economic Science Series, 267-275. Morgan, J. (2013, October 24). Women 'Better at Multitasking' than Men, Study Finds. Retrieved from Science Reporter, BBC News: https://www.bbc.com/news/science-environment-24645100 Mustajab, D., Bauw, A., Rasyid, A., Irawan, A., Muhammad, A., Akbar, M. A., & Hamid, M. A. (2020). Working from Home Phenomenon as an Effort to Prevent COVID-19 Attacks and Its Impacts on Work Productivity. The International Journal of Applied Business, 13-21. Nakrošienė, A., Bučiūnienė, I., & Goštautaitė, B. (2019). Working from Home: Characteristics and Outcomes of Telework. International Journal of Manpower, 1-22. Naughton, J. (2020, August 15). Working from Home was the Dream but is it Turning into a Nightmare? Retrieved from The Guardian: https://www.theguardian.com/commentisfree/2020/aug/15/working-from-home-was-the-dream-but-is-it-turning-into-a-nightmare Nayak, S., & Pandit, D. (2021). Potential of Telecommuting for Different Employees in the Indian Context Beyond COVID-19 Lockdown. Transport Policy, 98-110. Oakman, J., Kinsman, N., Stuckey, R., Graham, M., & Weale, V. (2020). A Rapid Review of Mental and Physical Health Effects of Working at Home: How Do We Optimise Health? BMC Public Health, 1-13. O'Connell, A. A. (2006). Logistic Regression Models for Ordinal Response Variables . Sage. OECD. (2021). Caregiving in Crisis: Gender Inequality in Paid and Unpaid During COVID-19 . Organisation for Economic Co-operation and Development. Óladóttir, Á. D., Christiansen, Þ. H., & Aðalsteinsson, G. D. (2021). If Iceland Is a Gender Paradise, Where Are the Women CEOs of Listed Companies? Exploring Gender at Work: Multiple Perspectives, 317-337. Parkes, A., Sweeting, H., & Wight, D. (2015). Parenting Stress and Parent Support Among Mothers with High and Low Education. Journal of Family Psychology, 907. Patwa, P. (2020, May 14). Is Work from Home the New Lifestyle Change That Young India Was Seeking? Retrieved from Entrepreneur India: https://www.entrepreneur.com/en-in/lifestyle/is-work-from-home-the-new-lifestyle-change-that-young-india/350630 Périvier, H. (2014). Men and Women During the Economic Crisis: Employment Trends in Eight European Countries. Revue de l’OFCE, 41-84. Petriglieri, G. (2020, July 15). In Praise of the Office. HBR- The New Reality of WFH. Harvard Business Review. Purwanto, A., Asbari, M., Fahlevi, M., Mufid, A., Agistiawati, E., Cahyono, Y., & Suryani, P. (2020). Impact of Work From Home (WFH) on Indonesian Teachers Performance during the Covid-19 Pandemic: An Exploratory Study. International Journal of Advanced Science and Technology, 6235–6244. Reichelt, M. M. (2021). The Impact of COVID-19 on Gender Inequality in the Labor Market and Gender-role Attitudes. European Societies, S228- S245. Ruppanner, L. (2015, August 15). Women Are Not Better at Multitasking. They Just Do More Work, Studies Show. Retrieved from THE CONVERSATION- Science Alert: https://www.sciencealert.com/women-aren-t-better-multitaskers-than-men-they-re-just-doing-more-wor Russell, S. (2019, October 28). Mental Health. Retrieved from World Economic Forum: https://www.weforum.org/agenda/2019/10/remote-working-from-home-increase-stress-anxiety-mental-health/ Saludin, N. A., & Hassan, H. (2012). A Conceptual Study on Working from Home in Malaysian Construction Industry. Saludin, N. A., & Hassan, H. (2012). International Proceedings of Economics Development and Research (pp. 67-72). IACSIT Press. Sevilla, A., Phimister, A., Krutikova, S., Kraftman, L., Farquharson, C., Dias, M. C., . . . Andrew, A. (2020). How are mothers and fathers balancing work and family under lockdown? Bristol: IFS Briefing Note; No. 290. Shafizadeh, K. R., Mokhtarian, P. L., Niemeier, D. A., & Salomon, I. (2020). The Costs and Benefits of Home-Based Telecommuting. California: Partners for Advanced Transit and Highways (PATH). Shahid, N., Asif, M., & Pasha, A. (2022). Effect of Internet Addiction on School Going Children. Inverge Journal of Social Sciences, 1(1), 13-55. Shareena, P., & Shahid, M. (2020). Work from home during COVID-19: Employees Perception and Experiences. Global Journal for Research Analysis, 1-3. Sharma, M. K., Amudhan, S., & Ganjekar, S. (2021). Webinar fatigue: Fallout of COVID-19. Journal of the Egyptian Public Health Association. Singer-Velush, N., Sherman, K., & Anderson, E. (2020, July 15). Microsoft Analyzed Data on Its Newly Remote Workforce- the New Realityof WFH. Harvard Business Review. Soman, S., & Mohanan, D. (2022). Home-based Work and Stress in the Pandemic Period: A Case of Working Women in Kerala. IIM Ranchi Journal of Management Studies, 160-174. Song, Y., & Gao, J. (2019). Does Telework Stress Employees Out? A Study on Working at Home and Subjective Well-Being for Wage/Salary Workers. Journal of Happiness Studies, 1-20. Stadtlander, L., Sickel, A., La Civita, L., & Giles, M. (2017). Home as Workplace: A Qualitative Case Study of Online Faculty Using Photovoice. Journal of Educational Research and Practice, 45–59. Stoet, G., O’Connor, D. B., Conner, M., & Laws, K. R. (2013). Are women Better than Men at Multi-tasking? BMC Psychology, 1-10. Szameitat, A. J., Hamaida, Y., Tulley, R. S., Saylik, R., & Otermans, P. C. (2015). “Women Are Better Than Men”–Public Beliefs on Gender Differences and Other Aspects in Multitasking. PLoS ONE , e0140371. Thorstensson, E. (2020). The Influence of Working from Home on Employees' Productivity: Comparative document analysis between the years 2000 and 2019-2020. Karlstad: Karlstad Business School, B-Thesis. Turmaud, D. R. (2020, December 31). The Science Behind Pandemic Fatigue. Retrieved from Psychology Today: https://www.psychologytoday.com/us/blog/lifting-the-veil-trauma/202012/the-science-behind-pandemic-fatigue Vander Elst, T., Verhoogen, R., Sercu, M., Van den Broeck, A., Baillien, E., & Godderis, L. (2017). Not Extent of Telecommuting, But Job Characteristics as Proximal Predictors of Work-related Well-being. Journal of Occupational and Environmental Medicine, e180-e186. Vlach, P., & Plašil, M. (2006). Analysis of Multiple-response Data. 9th International Scientific Conference on Applications of Mathematics and Statistics in Economics, (pp. 1-5). Vyas, L., & Butakhieo, N. (2021). The Impact of Working from Home During COVID-19 on Work and Life Domains: An Exploratory Study on Hong Kong. Policy Design and Practice, 59-76. Wang, V., & Inoue, M. (2020, March 4). New York Times. Retrieved from When Can we Go to School? Nearly 300 Million Children are Missing Class: https://www.nytimes.com/2020/03/04/world/coronavirus-schools-closed.html WEF. (2023). Global Gender Gap Report 2023. Geneva: World Economic Forum. Wienclaw, R. A. (2019). Telecommuting. Salem Press Encyclopedia.